Enhancement in the rate of the top seeded solution growth of SiC crystals via a roughening of the graphite surface. (8th May 2017) - Yoon, Ji-Young; Lee, Myung-Hyun; Kim, Younghee; Seo, Won-Seon; Shul, Yong-Gun; Lee, Won-Jae; Jeong, Seong-Min
Abstract: With the top seeded solution growth (TSSG) method, SiC crystals are grown in a Si–C solution where the dissolved C is supplied from graphite crucibles. In this study, the reactivity of the graphite was enhanced by roughening the surface to form a SiC interlayer, the intermediate compound in the dissolution of C to a Si melt. As a result, we clearly observed an enhancement in the growth rate by roughening the graphite surface in the crystal growth of SiC using TSSG method.